The Impact of Financial Stability and Audit Firm Affiliation on the Level of Disclosure of Sustainable Green Banking - Anggreni Dian Kurniawati; Anna Purwaningsih (Media Ekonomi dan Manajemen, 2024)
Green banking combines operational improvement, technological advancement, and modifications to client behavior in commercial banking. Activities in environmental, social, and corporate governance (ESG) management are part of the banking industry's adoption of sustainable green banking. The goal of ESG disclosure in banking organizations is to spur market growth, boost consumer confidence in banking goods and services, and give investors essential information for making investment decisions. This study intends to empirically demonstrate the impact of audit firm affiliation and financial stability on the degree of disclosure of sustainable green banking. A banking firm with an observation period of 2019–2022, listed on the Indonesia Stock Exchange, serves as the study's sample. The quantitative data used in this study were taken from published annual reports. Purposive sampling is a strategy used to obtain data. The study's independent variables are affiliation with an audit firm and financial stability as measured by return on equity (ROE). While the Environment, Social, and Governance Index (ESGI) will be used as a proxy for the dependent variable in this study, which is the degree of sustainable green banking. The natural logarithm of total assets is employed in this study's control variable for business size. The hypothesis being investigated is that the development of sustainable green accounting is positively influenced by financial stability and affiliation with audit firms. Several regression tests are used to evaluate this hypothesis. The findings of this study are intended to give banking organizations a general overview of the value of sustainable green banking in enhancing investor trust and improving their capacity to compete in the capital market.